PENGENALAN BUSINESS MODEL CANVAS DALAM PENGEMBANGAN USAHA BARBERSHOP DAVIDOF DI BEJI TIMUR DEPOK - Edalmen; Nuringsih, Kartika (Jurnal Serina Abdimas, 2023)
ABSTRACT The advancement of information and communication technology has become an important factor that is useful in various aspects. Everything that is done online also encourages progress in the field of information and communication technology. One form of product from information and communication technology is games. With the rapid development and popularity of games, it supports many game majors in college. At the high school level, especially upper secondary, game learning can be carried out through extracurricular activities. With extracurricular activities, high school students can develop their potential earlier and make the learning they get as a provision for entering the world of college later. This extracurricular activity also becomes one of the ways for students to support the improvement of non-academic achievements. Similar community service programs have been carried out previously for extracurricular teaching and have received a positive response. Sinar Dharma High School, which previously won a competition held through community service programs, now opens an extracurricular for game programming with Unity. The community service program is divided into several stages, namely needs research, material creation, teaching implementation, and final assessment. Along with the rise of entrepreneurial activity among young people, one of the businesses that attracts the attention of many beginners is a barbershop. Many beginners want to try starting this business, including "Davidof Barbershop" in East Beji, Depok. The business will be opened in September 2022 with the consideration that campuses around Depok have started hybrid or limited face-to-face meetings in the middle of that month. In practice there are many obstacles to retaining customers so that within two months of starting a business it has not shown satisfactory performance. To help partners carry out mentoring and socialization activities in the introduction of the business model canvas (BMC) as a framework (blueprint) to define business pilot models and learn to map the customer journey. The preparation of BMC aims to explain, assess, visualize, and change the business model so that business performance is maximized. Based on these considerations, an introduction to BMC was carried out as information for entrepreneurs who are starting a business. This matrix consists of the right side describing external aspects including customer segments, value propositions, channels, customer relationships and revenue streams. While the left side or the internal aspect includes key activities, key resources, key partnerships, and cost structure. The ability to understand the 9 blocks will support the smooth running of a business. Through this assistance and socialization, business actors can understand BMC as an initial stage in running a business, even though it is not easy to go through the pioneering  period of the business.   ABSTRAK Seiring maraknya aktivitas entrepreneurial di kalangan anak muda, salah satu usaha yang banyak dilirik pemula adalah barbershop. Banyak pemula ingin mencoba merintis usaha ini diantaranya “Davidof Barbershop” di Beji Timur, Depok. Usaha dibuka pada September 2022 dengan pertimbangan kampus di sekitar Depok sudah mulai hybrid atau tatap muka terbatas di pertengahan bulan tersebut. Dalam prakteknya banyak kendala mempertahankan pelanggan sehingga dalam dua bulan memulai usaha belum menunjukan kinerja yang memuaskan. Untuk membantu mitra dilakukan kegitan pendampingan dan sosialisasi dalam pengenalan business model canvas (BMC) sebagai kerangka kerja (blueprint) mendefinisikan model rintisan bisnis serta belajar memetakan customer journey. Penyusunan BMC bertujuan menjelaskan, menilai, memvisualisasikan serta mengubah model bisnis agar kinerja usaha menjadi maksimal. Atas pertimbangan tersebut, dilakukan kegiatan pengenalan BMC sebagai informasi bagi wirausaha yang sedang memulai usaha. Matrik ini terdiri bagian kanan menggambarkan aspek eksternal meliputi customer segments, value propositions, channels, customer relationship dan revenue streаm. Sedangkan bagian kiri atau aspek internal meliputi key аctivities, key resources, key pаrtnership dan cost structure. Kemampuan memahami ke-9 blok tersebut akan mendukung kelancaran dalam perintisan usaha. Melalui pendampingan dan sosialisasi ini pelaku usaha dapat memahami BMC sebagai tahapan awal dalam menjalankan usaha, meskipun dalam realisasinya tidak mudah menjalani masa rintisan bisnis tersebut.